The Development of Naringin for Use against Bone and Cartilage Disorders - Juwen Gan; Xiaolan Deng; Yonghong Le; Jun Lai; Xiaofei Liao (Molecules, 2023)
Bone and cartilage disorders are the leading causes of musculoskeletal disability. There is no absolute cure for all bone and cartilage disorders. The exploration of natural compounds for the potential therapeutic use against bone and cartilage disorders is proving promising. Among these natural chemicals, naringin, a flavanone glycoside, is a potential candidate due to its multifaceted pharmacological activities in bone and cartilage tissues. Emerging studies indicate that naringin may promote osteogenic differentiation, inhibit osteoclast formation, and exhibit protective effects against osteoporosis in vivo and in vitro. Many signaling pathways, such as BMP-2, Wnt/β-catenin, and VEGF/VEGFR, participate in the biological actions of naringin in mediating the pathological development of osteoporosis. In addition, the anti-inflammatory, anti-oxidative stress, and anti-apoptosis abilities of naringin also demonstrate its beneficial effects against bone and cartilage disorders, including intervertebral disc degeneration, osteoarthritis, rheumatoid arthritis, bone and cartilage tumors, and tibial dyschondroplasia. Naringin exhibits protective effects against bone and cartilage disorders. However, more efforts are still needed due to, at least in part, the uncertainty of drug targets. Further biological and pharmacological evaluations of naringin and its applications in bone tissue engineering, particularly its therapeutic effects against osteoporosis, might result in developing potential drug candidates.